Postoperative care fragmentation and thirty‐day unplanned readmissions after head and neck cancer surgery. (14th October 2016) - Graboyes, Evan M.; Kallogjeri, Dorina; Saeed, Mohammed J.; Olsen, Margaret A.; Nussenbaum, Brian
Abstract : Objectives/Hypothesis: Postdischarge care fragmentation, readmission to a hospital other than the one performing the surgery, has not been described in head and neck cancer patients. We sought to determine the frequency, risk factors, and outcomes for head and neck cancer patients experiencing postdischarge care fragmentation. Study Design: Retrospective cohort study. Methods: We analyzed patients in the 2008 to 2010 California State Inpatient Database with a 30‐day unplanned readmission following head and neck cancer surgery. The frequency of postdischarge care fragmentation, patient‐ and hospital‐level risk factors for care fragmentation, readmission diagnosis, and readmission outcomes were determined. Results: Of 561 patients with a 30‐day unplanned readmission, 210 (37.4%) were readmitted to a hospital other than the one performing the surgery. Surgical hospitalization length of stay ≥15 days (odds ratio [OR]: 1.87, 95% confidence interval [CI]: 1.13‐3.10) and discharge to a care facility (OR: 2.85, 95% CI: 1.77‐4.58) were associated with care fragmentation. Overall, 39.8% of unplanned 30‐day readmissions (223/561) were treatment complications, and 30.9% of treatment complication readmissions (69/223) occurred at a nonindex hospital. Patients with postdischarge care fragmentation had a 2.1‐fold increased risk of in‐hospital mortality within 30 days of readmission compared to patients readmitted to the index hospital (95% CI: 1.04‐4.26). Conclusions: Postdischarge care fragmentation following head an neck cancer surgery is common, as 37% of readmitted patients and 31% of patients readmitted with a treatment complication are readmitted to a hospital other than the surgical hospital. Head and neck cancer patients experiencing care fragmentation are at increased risk of in‐hospital mortality within 30 days of readmission. Level of Evidence: 4. Laryngoscope, 127:868–874, 2017